Pharmacognostic evaluation of leaves of Dysoxylum binectariferum - Rajesh Ankalge; Mangesh Jagdale; Sonali Ghaytidak; Kalpesh Patil; Lata Manani; Sonal Desai (Elsevier, 2021)
Background: Dysoxylum binectariferum is widely known for its medicinal properties. The leaves of this plant are major source of rohitukine, a precursor of the anti-cancer compound flavopiridol. Purpose: To provide standardization parameters for leaves of Dysoxylum binectariferum for identification of correct plant material and for preparation of monograph. Methods: Macroscopic evaluation, microscopic evaluation and powder characteristics of leaves of D. binectariferum were carried out. Physico-chemical parameters of leaves were also evaluated. Preliminary phytochemical analysis was carried out using various chemical tests. HPTLC fingerprints were obtained using Silica gel 60 F254 plates as stationary phase and toluene: ethyl acetate: formic acid (5:1.5: 0.5, v/v/v) as mobile phase. Heavy metals were evaluated by inductively coupled plasma-optical emission spectroscopy. Pesticides were determined by gas chromatography-mass spectroscopy. Aflatoxins were evaluated using HPTLC studies. Results: Macroscopy, microscopy and powder characteristics revealed presence of well-defined cellular structures. The ethanol soluble extractive and water-soluble extractive values were 11.2 ± 0.11 and 20.8 ± 0.23, respectively. The total ash, acid insoluble ash and water-soluble ash were found to be 10.73±0.95% w/w, 0.74±0.48% w/w and 3.35±1.07% w/w, respectively. The moisture content was found to be 19.0 ± 0.60% w/w. Extractive values of samples in different solvents such as methanol, ethanol, water, ethyl acetate, petroleum ether and chloroform were determined. Preliminary phytochemical screening of these extracts revealed the presence of steroids, tannins, flavonoids, alkaloids, glycosides and carbohydrates. The heavy metals were found to be in permissible limits. The plant material under study was free from pesticides and aflatoxins. Conclusion: The parameters studied above can be useful for identification and authentication of plant material of D. binectariferum.